(untitled) (Лучшие интеллектуальные исследования, 2025)
Аннотация: на ранних этапах реабилитации у детей с нарушениями слуха освещена коррекционная педагогическая работа. В частности, раскрывается вопрос о процессе и этапах воспитания и вопросах его коррекции. Abstract: correctional pedagogical work is highlighted in the early stages of rehabilitation in children with hearing impairments In particular, the question of the process and stages of education and issues of its correction is revealed.